2018
DOI: 10.3889/oamjms.2018.484
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia (AML) In Elderly: Cytogenetic Characteristics of Patients Treated At Hematology and Pediatric Oncology Center in Casablanca

Abstract: AIM:The goals of this paper are: to report the incidence of AML in elderly, to describe cytogenetic characteristics of this population, to observe rare and novel cytogenetic abnormalities and lastly, to compare our finding with that previously reported in the literature.METHODS:We conducted a retrospective analysis of 283 patients with acute myeloid leukaemia (AML) treated in our unit, we will report the incidence of AML in elderly, describe cytogenetic characteristics of this population, observe rare and nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(21 reference statements)
1
1
0
2
Order By: Relevance
“…This finding is consistent with other studies that reported a normal karyotype in 40% to 48% of patients with AML 48–51 . However, a complex karyotype (≥3 clonal abnormalities) was detected in 27% of the patients who received the test, which is higher than that found in the previous studies 50,52,53 . A possible explanation for these results is that more than 55% of the patients in this study with AML were 65 years or older.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with other studies that reported a normal karyotype in 40% to 48% of patients with AML 48–51 . However, a complex karyotype (≥3 clonal abnormalities) was detected in 27% of the patients who received the test, which is higher than that found in the previous studies 50,52,53 . A possible explanation for these results is that more than 55% of the patients in this study with AML were 65 years or older.…”
Section: Discussionsupporting
confidence: 92%
“…[48][49][50][51] However, a complex karyotype (≥3 clonal abnormalities) was detected in 27% of the patients who received the test, which is higher than that found in the previous studies. 50,52,53 A possible explanation for these results is that more than 55% of the patients in this study with AML were 65 years or older. Studies have shown that older patients have more complex karyotypes than younger patients.…”
Section: Prognostic Markers In Cllmentioning
confidence: 82%
“…(5)(6)(7) En su desarrollo se produce la pérdida de respuesta a los reguladores normales de la proliferación celular en la medula ósea; lo que lleva a una aceleración del incremento de la población de células hemáticas inmaduras, desplazándose a la población celular normal, produciéndose una falla medular además de una infiltración extramedular que puede afectar el bazo, hígado, piel y sistema nervioso central. (2,6) La exposición reiterada al benceno está identificada como un potencial factor de riesgo de LMA, debido a la capacidad de dañar el ADN de las células normales de la médula ósea. Otra posible causa se ha identificado en el tratamiento de quimioterapia (en especial con fármacos alquilantes o inhibidores de la topoisomerasa II) o de radioterapia de otros tipos de cáncer como el linfoma, el mieloma y el de seno.…”
Section: Discussionunclassified
“…Su tratamiento es complejo sobre todo al asociarse con comorbilidad y fragilidad. (1,2) Aproximadamente, el 70-80% de los pacientes menores de 60 años logra remisión completa, su supervivencia global por 5 años se establece en el 40-45%, pero la mediana al respecto se establece en un año. (1) Las expectativas para estos pacientes no han cambiado en las tres últimas décadas, siendo peor en aquellos con perfil citogenético desfavorable asociado con el detrimento de la respuesta inmunitaria secundaria al proceso de inmunoscenecencia.…”
Section: Introductionunclassified